2013
DOI: 10.1016/j.jval.2013.03.1509
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of non-administration of ordered doses of venous thromboembolism prophylaxis: implications for novel intervention strategies

Abstract: A291telephone counseling can significantly improve blood pressure control. Our data show also that interventions run by allied health professionals (i.e. other than the prescriber/doctor), improve adherence to medicines and promote hypertension-related health behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…These efforts were made with the implicit and incorrect assumption that prescribed medication doses will always be administered to patients, when in fact patient refusal is a leading cause of nonadministration. Studies of VTE prophylaxis administration have reported that 10% to 12% of doses are not administered to patients . Alarmingly, it has been reported that among medically ill patients, between 10% and 30% of doses are not administered, with patient refusal as the most frequently documented reason.…”
mentioning
confidence: 99%
“…These efforts were made with the implicit and incorrect assumption that prescribed medication doses will always be administered to patients, when in fact patient refusal is a leading cause of nonadministration. Studies of VTE prophylaxis administration have reported that 10% to 12% of doses are not administered to patients . Alarmingly, it has been reported that among medically ill patients, between 10% and 30% of doses are not administered, with patient refusal as the most frequently documented reason.…”
mentioning
confidence: 99%
“…Nonetheless, a sensitivity analysis demonstrated that the reduction in symptomatic VTE remains valid. Another limitation of our study is that it evaluated the prescription of VTE prophylaxis but not its actual administration, which may also have an effect on efficacy of prophylaxis . Our study also had a limited number of cancer and stroke patients, and.…”
Section: Discussionmentioning
confidence: 99%
“…Akut DVT ve PE'nin tedavisi ve tekrarlayan VTE'nin önlenmesi, öncelikle antikoagülan tedavi kullanılmasını gerektirmektedir. Tedavi için güncel bakım standardı ise genellikle düşük moleküler ağırlıklı heparin ile yapılan tipik bir K vitamini antagonistidir (Fanikos et al, 2010;Shermock et al 2013). VTE'nin insidansının ve ekonomik yükünün arttığı, VTE kaynaklı mortalitenin ise tedavi maliyetlerini arttırdığı, sağlık sistemlerine ekonomik yük getirdiği ifade edilebilir (Fanikos et al, 2013).…”
Section: Igi̇ri̇şunclassified